Simple Computational Method of Predicting Electrical Characteristics in Solar Cells - Ma, J.; Man, K. L.; Ting, T. O.; Zhang, N.; Lim, E. G.; Guan, Sheng-Uei; Wong, P. W.H.; Krilavicius, T.; Saulevicius, D.; Lei, C. U. (Elektronika ir Elektrotechnika, 2014)
A precise single-diode analytical model of Photovoltaic (PV) modules is generally nonlinear analytical equations with high computation complexity. This paper proposes a simple computational method for the PV model. Its exponential diode behaviour is simplified via Least Squares Approximation (LSA), which permits designers or engineers to predict the electrical characteristics of a PV module without using iterative numerical calculations. Based on experimental data, the methodology is validated by covering a wide range of operation conditions. Simulation and experimental results prove the effectiveness and accuracy of the proposed method. DOI: http://dx.doi.org/10.5755/j01.eee.20.1.6165